Micro/nano-structured TiO2 surface with dual-functional antibacterial effects for biomedical applications - Xiang Ge; Chengzu Ren; Yonghui Ding; Guang Chen; Xiong Lu; Kefeng Wang; Fuzeng Ren; Meng Yang; Zhuochen Wang; Junlan Li; Xinxin An; Bao Qian; et al. (Bioactive Materials, 2019)
Implant-associated infections are generally difficult to cure owing to the bacterial antibiotic resistance which is attributed to the widespread usage of antibiotics. Given the global threat and increasing influence of antibiotic resistance, there is an urgent demand to explore novel antibacterial strategies other than using antibiotics. Recently, using a certain surface topography to provide a more persistent antibacterial solution attracts more and more attention. However, the clinical application of biomimetic nano-pillar array is not satisfactory, mainly because its antibacterial ability against Gram-positive strain is not good enough. Thus, the pillar array should be equipped with other antibacterial agents to fulfill the bacteriostatic and bactericidal requirements of clinical application. Here, we designed a novel model substrate which was a combination of periodic micro/nano-pillar array and TiO2 for basically understanding the topographical bacteriostatic effects of periodic micro/nano-pillar array and the photocatalytic bactericidal activity of TiO2. Such innovation may potentially exert the synergistic effects by integrating the persistent topographical antibacterial activity and the non-invasive X-ray induced photocatalytic antibacterial property of TiO2 to combat against antibiotic-resistant implant-associated infections. First, to separately verify the topographical antibacterial activity of TiO2 periodic micro/nano-pillar array, we systematically investigated its effects on bacterial adhesion, growth, proliferation, and viability in the dark without involving the photocatalysis of TiO2. The pillar array with sub-micron motif size can significantly inhibit the adhesion, growth, and proliferation of Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). Such antibacterial ability is mainly attributed to a spatial confinement size-effect and limited contact area availability generated by the special topography of pillar array. Moreover, the pillar array is not lethal to S. aureus and E. coli in 24 h. Then, the X-ray induced photocatalytic antibacterial property of TiO2 periodic micro/nano-pillar array in vitro and in vivo will be systematically studied in a future work. This study could shed light on the direction of surface topography design for future medical implants to combat against antibiotic-resistant implant-associated infections without using antibiotics. Keywords: Titanium dioxide, Micro/nano-structured surface, Topographical bacteriostatic activity, Photocatalytic bactericidal property, Non-invasive treatment